2019
DOI: 10.1186/s12913-019-4530-2
|View full text |Cite
|
Sign up to set email alerts
|

Costs of hospitalization for stroke from two urban health insurance claims data in Guangzhou City, southern China

Abstract: Background Stroke remains a major global health problem. In China, stroke was the leading cause of death and imposed a large impact on the healthcare system. This study aimed to examine the hospitalization costs by five stroke types and the associated factors for inpatient costs of stroke in Guangzhou City, Southern China. Methods This was a prevalence-based, cross-sectional study. Data were obtained from urban health insurance claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 40 publications
6
41
2
Order By: Relevance
“…This is a 3-year cross-sectional study designed to evaluate the health service utilization of stroke patients according to the different cities’ health insurance schemes. Between 2014 and 2016, we obtained all related information on patients whose primary diagnosis was stroke according to ICD-10 (ischemic stroke (I63), hemorrhagic stroke (I60, I61, I62, G45) and other types of stroke (I64, I67-I69, 7, 10) [ 19 ]. The final sample included 69,054 patients and 203,697 admissions, including 52,412 patients who were insured by UEBMI and 16,642 patients who were covered by URBMI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a 3-year cross-sectional study designed to evaluate the health service utilization of stroke patients according to the different cities’ health insurance schemes. Between 2014 and 2016, we obtained all related information on patients whose primary diagnosis was stroke according to ICD-10 (ischemic stroke (I63), hemorrhagic stroke (I60, I61, I62, G45) and other types of stroke (I64, I67-I69, 7, 10) [ 19 ]. The final sample included 69,054 patients and 203,697 admissions, including 52,412 patients who were insured by UEBMI and 16,642 patients who were covered by URBMI.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the coverage, benefit schedule and reimbursements, a patient’s health insurance scheme impacted the financial burden of stroke on families [ 19 ]. Insurance scheme provided a safety net from financial loss, depending on the scope and incentives or disincentives for patients to consume health services [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And in China, the newest evidence showed that nearly 2% of total health expenditures of urban residents were spent on stroke-related medical costs [ 3 ]. Previous studies have assessed medical costs for stroke patients in some specific cities in China: In Guangzhou, the average medical costs was $3212.1 from 2006 to 2013 [ 4 ], and it was calculated as $3052.7 in Beijing city in 2012 [ 5 ]. It seemed that geographic variation in stroke patients’ medical costs widely existed in China.…”
Section: Introductionmentioning
confidence: 99%
“…Covering more than 95% of the residents in urban China during the 2013-2016 period, the two schemes covered roughly 750 million, or 54%, of the total Chinese population [12].The basic differences between UEBMI and URBMI are set out in Table 1.UEBMI is funded both by employers (2% of wages) and employees (6% of annual wages) [13], while the revenue for the URBMI is from individual premium contributions and subsides from central and local government.As shown in Table 1, UEBMIprovides better nancial protection and offers a more comprehensive coverage than URBMI, which focuses on inpatient services, catastrophic illness insurance, but withlimited coverage of basic outpatient services [14]. Patients with UEBMI usually utilize more health services and have higher expense than those with URBMI [15].…”
Section: Introductionmentioning
confidence: 99%